A devida diligência obrigatória em direitos humanos - Vasconcelos, Enderson Danilo Santos de (2024)
Cases of human rights violations have increased in the last century. The need for greater production of goods and services implies greater depletion of natural and human resources, resulting in negative externalities with severe damage to the environment and individuals. These impacts are caused by companies, notably transnational companies, which requires greater reflection on the possibility of demanding the exercise of ethical and responsible behavior. Corporate responsibility, however, cannot be limited to the confirmation or simple dissemination of the fact that human rights are respected, under penalty of incurring the capture of these values by the market, converting them into economic language. The UN guiding principles for business and human rights occupy this space, although they are the object of criticism for their voluntariness. There is no doubt that parameters should be sought; the problem lies in how to impose them on companies without violating the legal order, notably the principle of legality. In this scenario, due diligence in human rights presents itself as a useful tool, as it leads companies to adopt responsible behavior oriented towards respect for human rights. Due diligence is an ongoing and proactive process through which companies can learn about the risks or impacts on human rights that are being caused, so that they can take action to mitigate, prevent or repair them. Due diligence operates precisely in an area of uncertainty and lack of knowledge on the part of the company, and is the only way that allows it to demonstrate that it respects human rights. Given the importance of the tool, the question is whether it is possible to attribute it to mandatory status under the current legal system. This implies defining how due diligence should operate in the national scenario in the face of corporate activity, even in the case of transnational companies. Thus, this paper aims to answer this question, especially based on the analysis of the principles and foundations of the economic order provided for in the Federal Constitution and interpretative keys such as the dignity of the human person and the horizontal effectiveness of human rights. The analysis of the problem required that aspects related to corporate behavior, business ethics and other instruments used to address human rights violations be considered. To prepare this work, the hypothetical-deductive method was used, with the aid of bibliographic research as a methodological procedure. Thus, the aim was to identify a valid legal basis for the existence of a duty of care attributable to companies in relation to human rights and, mainly, whether it is possible to defend the existence of a constitutional duty of due diligence in human rights.